M-bit bimetallic MAX-phase wave-absorbing material and preparation method thereof
By preparing the M-position bimetallic MAX phase absorbing material with chemical expression (Ti2-xMx) GaC, the problem of lack of M-position bimetallic MAX phase absorbing material in existing ceramic materials is solved, and the effects of low reflection loss and thin matching thickness are achieved, which improves its performance in the field of electromagnetic wave absorption and shielding.
Patent Information
- Application Number
- CN202411463428.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-03-07
AI Technical Summary
The lack of M-position bimetallic MAX phase absorbing material in existing ceramic materials leads to poor impedance matching, thick matching thickness and single loss mechanism in electromagnetic wave absorption, which limits its performance improvement in practical applications.
A M-position bimetallic MAX phase absorbing material with a chemical expression (Ti2-xMx) GaC is used, and its M elements are V, Nb and Ta, 0
The preparation of M-position bimetallic MAX phase absorbing material has been realized, with low reflection loss, thin matching thickness and broad application prospects, significantly improving its performance in the field of electromagnetic wave absorption and shielding.
Smart Images

Figure CN119569057A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials and is an M-position bimetallic MAX phase wave absorbing material and a preparation method thereof. Background Art
[0002] With the rapid development of information technology and electronic communications, the problem of electromagnetic wave radiation pollution is becoming increasingly serious; it poses a serious threat to human health, ecological environment and national security, and has become a global challenge. In order to meet this challenge, the development of high-performance electromagnetic wave absorbing materials has become an effective solution. The ideal absorbing material should have strong absorption capacity, matching thin thickness and wide absorption bandwidth; among them, the ternary layered MAX phase, which has both metallic and ceramic properties, provides a new way for the exploration and application of electromagnetic wave absorbing materials. MAX phase refers to a class of nano-layered compounds composed of transition metals, which has a hexagonal lattice structure; its chemical formula is M n+1 AX n , where M represents a transition metal of the early transition series, A represents a main group element, X represents carbon and / or nitrogen, and n ranges from 1 to 3. The crystal structure of the MAX phase exhibits hexagonal symmetry and belongs to the space group P63 / mmc; it consists of nanolayer sublayers M n+1 X n and A-site monoatomic layers are stacked alternately. n+1 X n The sublayer is composed of covalently bonded M6X octahedral layers, while the A atomic layer is connected to the M n+1 X n The interaction between the sublayers is relatively weak, resulting in an approximately metallic bonding state. The unique layered structure and bonding characteristics of the MAX phase give it both metallic and ceramic properties. Therefore, the MAX phase has good application prospects in electromagnetic microwave absorption, such as Ti3AlC2, Ti3SiC2 and Cr2AlC. However, poor impedance matching, thick matching thickness and single loss mechanism behavior seriously hinder the further improvement of its electromagnetic microwave absorption performance.
[0003] To solve the above problems, researchers have implemented strategies such as morphology control, grain size optimization, chemical regulation, and composite technology; generally speaking, the ability of MAX phases to absorb electromagnetic waves is mainly affected by their inherent electronic structure. The electronic band structure is mainly determined by the outermost d electrons of the early transition metal atoms located at the M site, which plays a crucial role in the inherent properties of MAX phases. On the one hand, impedance matching depends on complex parameters of permittivity and permeability, and is fine-tuned by adjusting the composition of elements at the M site in MAX phases; on the other hand, by controlling the chemical composition of elements at the M site, especially through the bimetallic method, various types of polarization losses are introduced, and the presence of defects and perturbations is increased. These perturbation centers act as polarization centers. Therefore, controlling the chemical composition of elements at the M site in MAX phases is an effective strategy to enhance their absorption ability, but there are few M-site bimetallic MAX-phase microwave absorbing materials in the field of existing ceramic materials technology. Summary of the Invention
[0004] To overcome the above deficiencies, the object of the present invention is to provide a bimetallic MAX-phase microwave absorbing material at the M site and its preparation method to the art, so as to solve the problem that there is a lack of M-site bimetallic MAX-phase microwave absorbing materials in existing ceramic materials and it is difficult to have efficient electromagnetic wave absorption characteristics. Specifically, the existing MAX-phase microwave absorbing agents have problems such as poor impedance matching, thick matching thickness, and single loss mechanism, which hinder the practical application of MAX-phase microwave absorbing agents. Its object is achieved through the following technical solutions.
[0005] A bimetallic MAX-phase microwave absorbing material at the M site, characterized in that the chemical formula of the material is (Ti 2-x M x )GaC, the M element is one of V, Nb, and Ta elements, and 0 < x < 2. This material is mainly applied in the fields of electromagnetic wave absorption and shielding, and for the first time realizes the preparation of M-site bimetallic MAX-phase microwave absorbing materials, with advantages such as low cost and simple preparation method; compared with ternary MAX-phase microwave absorbing agents, it has the advantages of low reflection loss and thin matching thickness, greatly improving the problem of poor impedance matching of MAX phases, and has broad application prospects.
[0006] Preferably, (Ti 2-x M x )GaC has a hexagonal crystal structure, the space group is P63 / mmc, and the unit cell is alternately stacked by (Ti 2- x M x )C units and Ga atomic layers.
[0007] Preferably, the minimum reflection loss of this material is -56.1 dB, the matching thickness is 1.06 mm; the maximum effective absorption bandwidth is 4.48 GHz.
[0008] The specific steps of the preparation method of the material are as follows:
[0009] 1) mixing Ti material, M material, Ga material and C material in a molar ratio of (2-x):(x):1:1;
[0010] 2) The mixture is placed in an inert atmosphere and heated at 900-1500°C for 60-720 min to obtain the M-site bimetallic MAX phase (Ti 2-x M x )GaC.
[0011] Preferably, the Ti material includes Ti single substance and / or an alloy containing Ti; the M material includes M single substance and / or an alloy containing M; and the X material includes C single substance and / or a compound containing C.
[0012] Preferably, the prepared M-site bimetallic MAX phase (Ti 2-x M x )GaC is taken out as the reaction product after it cools to room temperature, and the reaction product is washed with deionized water and dilute hydrochloric acid: the reaction product is placed in a beaker, deionized water is added, stirred and ultrasonically cleaned for 30 minutes, then allowed to stand for 1 hour, and the supernatant is poured out; after washing the reaction product three times, it is washed with ethanol and placed in an oven at 40°C, and taken out after 12 hours to obtain a solid product.
[0013] The material of the present invention is easy to produce and prepare, has good electromagnetic wave and other radiation absorption effects, is suitable for use as a wave-absorbing ceramic material, and is an improvement of similar materials; in particular, compared with the prior art, the beneficial effects of the present invention are: 1) the preparation method of the present invention is simple, and the prepared M-site bimetallic MAX phase material (Ti 2-x M x )GaC has high purity and is mainly used in the fields of electromagnetic wave absorption and shielding; 2) The M-site bimetallic MAX phase material (Ti 2-x M x )GaC has a minimum reflection loss of -56.1dB and a minimum matching thickness of only 1.06mm, which exceeds the performance of most MAX phase-based absorbing materials and has broad application prospects in the fields of electromagnetic wave absorption and shielding. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is the embodiment 4 of the present invention (Ti 1.7 V 0.3 ) Reflectivity curve of GaCMAX phase;
[0015] Figure 2 is the embodiment 4 of the present invention (Ti 1.7 V 0.3 )XRD pattern of GaCMAX phase;
[0016] Figure 3 is the embodiment 4 of the present invention (Ti 1.7 V 0.3 )Reflection loss values of GaCMAX phase at different thicknesses;
[0017] Figure 4 is the embodiment of the present invention 5 (Ti 1.6 V 0.4 )Reflection loss values of GaCMAX phase at different thicknesses;
[0018] Figure 5 is the embodiment 6 of the present invention (Ti 1.7 Nb 0.3 )XRD pattern of GaC;
[0019] Figure 6 is the embodiment 6 of the present invention (Ti 1.7 Nb 0.3 )Reflection loss values of GaCMAX phase at different thicknesses;
[0020] Figure 7 is the embodiment 7 of the present invention (Ti 1.7 Ta 0.3 )XRD pattern of GaC;
[0021] Figure 8 is the embodiment 7 of the present invention (Ti 1.7 Ta 0.3 )Reflection loss values of GaCMAX phase at different thicknesses. Implementation
[0023] The technical solution of the present invention is now further described in conjunction with the accompanying drawings and specific embodiments of the present invention, but the present invention is not limited to these embodiments.
[0024] Unless otherwise specified, the materials used in the present invention are conventional commercial products, and the methods used are conventional technical means.
[0025] Example 1
[0026] The preparation method of the MAX phase material of this embodiment includes:
[0027] (1) mixing Ti powder with a particle size of 300 mesh, V powder with a particle size of 300 mesh, Ga particles and graphite powder with a particle size of 300 mesh in a molar ratio of 1:1:1:1, and grinding and mixing;
[0028] (2) placing the mixed powder in a corundum crucible and placing it in a high-temperature tube furnace for reaction; the reaction conditions are: 900° C., 720 minutes, argon protection, and after the temperature of the tube furnace drops to room temperature, taking out the reaction product in the crucible;
[0029] (3) Washing the reaction product with deionized water and dilute hydrochloric acid: put the reaction product into a beaker, add deionized water, stir and ultrasonically clean for 30 minutes, then let it stand for 1 hour, and pour out the supernatant; wash the reaction product three times, then wash it with ethanol and put it into a 40°C oven, take it out after 12 hours, and obtain a solid product.
[0030] Example 2
[0031] The preparation method of the MAX phase material of this embodiment includes:
[0032] (1) mixing Ti powder with a particle size of 300 mesh, V powder with a particle size of 300 mesh, Ga particles and graphite powder with a particle size of 300 mesh in a molar ratio of 1.9:0.1:1:1, and grinding and mixing;
[0033] (2) placing the mixed powder in a corundum crucible and placing it in a high-temperature tube furnace for reaction; the reaction conditions are: 900° C., 720 minutes, argon protection, and after the temperature of the tube furnace drops to room temperature, taking out the reaction product in the crucible;
[0034] (3) Washing the reaction product with deionized water and dilute hydrochloric acid: put the reaction product into a beaker, add deionized water, stir and ultrasonically clean for 30 minutes, then let it stand for 1 hour, and pour out the supernatant; wash the reaction product three times, then wash it with ethanol and put it into a 40°C oven, take it out after 12 hours, and obtain a solid product.
[0035] Example 3
[0036] The preparation method of the MAX phase material of this embodiment includes:
[0037] (1) mixing Ti powder with a particle size of 300 mesh, V powder with a particle size of 300 mesh, Ga particles and graphite powder with a particle size of 300 mesh in a molar ratio of 0.1:1.9:1:1, and grinding and mixing;
[0038] (2) placing the mixed powder in a corundum crucible and placing it in a high-temperature tube furnace for reaction; the reaction conditions are: 1200° C., 240 minutes, argon protection, and after the temperature of the tube furnace drops to room temperature, taking out the reaction product in the crucible;
[0039] (3) Washing the reaction product with deionized water and dilute hydrochloric acid: put the reaction product into a beaker, add deionized water, stir and ultrasonically clean for 30 minutes, then let it stand for 1 hour, and pour out the supernatant; wash the reaction product three times, then wash it with ethanol and put it into a 40°C oven, take it out after 12 hours, and obtain a solid product.
[0040] Example 4
[0041] The preparation method of the MAX phase material of this embodiment includes:
[0042] (1) mixing Ti powder with a particle size of 300 mesh, V powder with a particle size of 300 mesh, Ga particles and graphite powder with a particle size of 300 mesh in a molar ratio of 1.7:0.3:1:1, and grinding and mixing;
[0043] (2) placing the mixed powder in a corundum crucible and placing it in a high-temperature tube furnace for reaction; the reaction conditions are: 1500° C., 60 minutes, argon protection, and after the temperature of the tube furnace drops to room temperature, taking out the reaction product in the crucible;
[0044] (3) Washing the reaction product with deionized water and dilute hydrochloric acid: put the reaction product into a beaker, add deionized water, stir and ultrasonically clean for 30 minutes, then let it stand for 1 hour, and pour out the supernatant; wash the reaction product three times, then wash it with ethanol and put it into a 40°C oven, take it out after 12 hours, and obtain a solid product.
[0045] Figure 1 The M-site bimetallic MAX phase material (Ti 1.7 V 0.3 )GaC reflectivity curve, from which it can be seen that the minimum reflection loss is -56.1dB; Figure 2 The M-site bimetallic MAX phase material (Ti 1.7 V 0.3 )GaC XRD diagram, from the XRD diagram, it can be seen that the obtained phase has a 211MAX phase characteristic peak, indicating that (Ti 1.7 V 0.3 )GaCMAX phase.
[0046] Figure 3 For the MAX phase material (Ti 1.7 V 0.3 )GaC reflection loss values at different thicknesses; the results show that the (Ti 1.7 V 0.3 )GaC has excellent electromagnetic wave absorption performance (-56.1dB, 1.06mm), and the effective absorption frequency band can reach 3.5GHz.
[0047] Example 5
[0048] The preparation method of the MAX phase material of this embodiment includes:
[0049] (1) mixing Ti powder with a particle size of 300 mesh, V powder with a particle size of 300 mesh, Ga particles and graphite powder with a particle size of 300 mesh in a molar ratio of 1.4:0.6:1:1, and grinding and mixing;
[0050] (2) placing the mixed powder in a corundum crucible and placing it in a high-temperature tube furnace for reaction; the reaction conditions are: 1300° C., 360 minutes, argon protection, and after the temperature of the tube furnace drops to room temperature, taking out the reaction product in the crucible;
[0051] (3) Washing the reaction product with deionized water and dilute hydrochloric acid: put the reaction product into a beaker, add deionized water, stir and ultrasonically clean for 30 minutes, then let it stand for 1 hour, and pour out the supernatant; wash the reaction product three times, then wash it with ethanol and put it into a 40°C oven, take it out after 12 hours, and obtain a solid product.
[0052] Figure 4 For the MAX phase material (Ti 1.4 V 0.6 )GaC reflection loss value at different thicknesses; the results show that the material synthesized in this embodiment (Ti 1.4 V 0.6 )GaC has excellent electromagnetic wave absorption performance (-43.6dB, 1.57mm), and the effective absorption frequency band can reach 4.48GHz.
[0053] Example 6
[0054] The preparation method of the MAX phase material of this embodiment includes:
[0055] (1) mixing Ti powder with a particle size of 300 mesh, Nb powder with a particle size of 300 mesh, Ga particles and graphite powder with a particle size of 300 mesh in a molar ratio of 1.7:0.3:1:1, and grinding and mixing;
[0056] (2) placing the mixed powder in a corundum crucible and placing it in a high-temperature tube furnace for reaction; the reaction conditions are: 1250° C., 600 minutes, argon protection, and after the temperature of the tube furnace drops to room temperature, taking out the reaction product in the crucible;
[0057] (3) Washing the reaction product with deionized water and dilute hydrochloric acid: put the reaction product into a beaker, add deionized water, stir and ultrasonically clean for 30 minutes, then let it stand for 1 hour, and pour out the supernatant; wash the reaction product three times, then wash it with ethanol and put it into a 40°C oven, take it out after 12 hours, and obtain a solid product.
[0058] Figure 5 The M-site bimetallic MAX phase material (Ti 1.7 Nb 0.3 )GaC XRD diagram, from the XRD diagram, it can be seen that the obtained phase has a 211MAX phase characteristic peak, indicating that (Ti 1.7 Nb 0.3 )GaCMAX phase.
[0059] Figure 6For the MAX phase material (Ti 1.7 Nb 0.3 )GaC reflection loss values at different thicknesses; the results show that the (Ti 1.7 V 0.3 )GaC has excellent electromagnetic wave absorption performance (-30.8dB, 4mm), and the effective absorption frequency band can reach 2.66GHz.
[0060] Example 7
[0061] The preparation method of the MAX phase material of this embodiment includes:
[0062] (1) mixing Ti powder with a particle size of 300 mesh, Nb powder with a particle size of 300 mesh, Ga particles and graphite powder with a particle size of 300 mesh in a molar ratio of 1.7:0.3:1:1, and grinding and mixing;
[0063] (2) placing the mixed powder in a corundum crucible and placing it in a high-temperature tube furnace for reaction; the reaction conditions are: 1250° C., 600 minutes, argon protection, and after the temperature of the tube furnace drops to room temperature, taking out the reaction product in the crucible;
[0064] (3) Washing the reaction product with deionized water and dilute hydrochloric acid: put the reaction product into a beaker, add deionized water, stir and ultrasonically clean for 30 minutes, then let it stand for 1 hour, and pour out the supernatant; wash the reaction product three times, then wash it with ethanol and put it into a 40°C oven, take it out after 12 hours, and obtain a solid product.
[0065] Figure 7 The M-site bimetallic MAX phase material (Ti 1.7 Nb 0.3 )GaC XRD diagram, from the XRD diagram, it can be seen that the obtained phase has a 211MAX phase characteristic peak, indicating that (Ti 1.7 Ta 0.3 )GaCMAX phase.
[0066] Figure 8 For the MAX phase material (Ti 1.7 Nb 0.3 )GaC reflection loss values at different thicknesses; the results show that the (Ti 1.7 Ta 0.3 )GaC has excellent electromagnetic wave absorption performance (-48.2dB, 3.5mm), and the effective absorption frequency band can reach 3.1GHz.
[0067] The specific embodiments described herein are merely examples of the spirit of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the spirit of the present invention or exceed the scope defined by the attached claims. Corresponding modifications and equivalent replacements shall be included in the protection scope of the present invention.
Claims
1. An M-position bimetallic MAX phase absorbing material, characterized in that: The chemical expression of this material is (Ti 2-x M x )GaC, the M element is one of V, Nb and Ta elements, and 0 <x<2。 2. The M-position bimetallic MAX phase absorbing material according to claim 1, characterized in that: The 2-x M x )GaC has a hexagonal structure with a space group of P63 / mmc. The unit cell is composed of (Ti 2-x M x )C units and Ga atomic layers are stacked alternately.
3. The M-position bimetallic MAX phase absorbing material according to claim 2, characterized in that: The material has a minimum reflection loss of -56.1dB and a matching thickness of 1.06mm; the maximum effective absorption bandwidth is 4.48GHz.
4. The method for preparing the M-position bimetallic MAX phase absorbing material according to claim 1, characterized in that: The specific steps of the preparation method of the material are as follows: 1) mixing Ti material, M material, Ga material and C material in a molar ratio of (2-x):(x):1:1; 2) The mixture is placed in an inert atmosphere and heated at 900-1500°C for 60-720 min to obtain the M-site bimetallic MAX phase (Ti 2-x M x )GaC.
5. The method for preparing the M-position bimetallic MAX phase absorbing material according to claim 4, characterized in that: The Ti material includes Ti single substance and / or an alloy containing Ti; the M material includes M single substance and / or an alloy containing M; and the X material includes C single substance and / or a compound containing C.
6. The method for preparing the M-position bimetallic MAX phase absorbing material according to claim 4, characterized in that: The M-site bimetallic MAX phase (Ti 2-x M x )GaC is taken out as the reaction product after it cools to room temperature, and the reaction product is washed with deionized water and dilute hydrochloric acid: the reaction product is placed in a beaker, deionized water is added, stirred and ultrasonically cleaned for 30 minutes, then allowed to stand for 1 hour, and the supernatant is poured out; after washing the reaction product three times, it is washed with ethanol and placed in an oven at 40°C, and taken out after 12 hours to obtain a solid product.